Risk factor of growth faltering in infants aged 2-12 months - Rina Pratiwi; Adriyan Pramono; Galuh Hardaningsih (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Growth faltering is a condition of growth disturbance that marked by slower growth velocity compared with previous growth chart. Growth faltering can cause effects in immune response, cognitive, & physical and psychomotor disturbance, behavioral disorder, learning problems, higher risk of infection and mortality.Objectives: To analyze risk factor of growth faltering in infant aged 2-12 months.Materials and Methods: A case control study was conducted in Public Health Center in Semarang city. Subject were infants aged 2 until 12 months with growth faltering. Variables were divided to exclusive breastfeeding, mother’s education, mother’s employment, social economic status, infection, mother’s nutrition and gestational age. Anthropometric and questionnaire data were obtained and analyzed among 116 infants. Statistic test used Chi square and multivariate analysis.Results: Chi-square analysis showed that breastfeeding (p=0.016) and gender (p=0.04) had a significant relationship with growth faltering in infant 2-12 months. Under standard parent’s income (p=0.809), Acute Respiratory Tract Infection (ARTI) (p=0.377), diarrhea (p=0.243), mother’s nutrition (p=1.00), gestational age (p=0.77), low mother’s education (p=0.83) and working mother (p=0.26) didn’t have a significant relationship with growth faltering in infant aged 2-12 months. Multivariate analysis showed that gender (p=0.035) and breastfeeding (p=0.019) were the most influencing variable to growth faltering. In 2-6 group, breastfeeding pattern had significant relationship with growth faltering (p=0.77)Conclusions: Breastfeeding and gender were risk factors of growth faltering in infant aged 2-12 months. Further research needed on how to prevent growth faltering in first 1000 days of life so it may avoid stunting in later life.